Pengaruh Sektor Agrikultur Dan Investasi Asing Langsung Terhadap Penerimaan Pajak Dengan Dimoderasi Kualitas Peraturan - Emilio Pascal; Suparna Wijaya (Journal of Law, Administration, and Social Science, 2023)
This study aims to analyze the effect of the agricultural sector and FDI on tax revenues in N-11 countries. Apart from that, the moderating variable of regulatory quality is also added. Data was obtained from World Development Indicators, World Bank and analyzed using panel data regression. The dependent variable in this study is tax revenue, while the independent variables include the agricultural sector, FDI, the agricultural sector which is moderated by the regulatory quality, FDI which is moderated by the regulatory quality, and regulatory quality. The results of the study show that all independent variables have a simultaneous effect on tax revenues. However, if you look at it partially, then FDI, the agricultural sector which is moderated by the regulatory quality and regulatory quality positively affects tax revenues. FDI which is moderated by the regulatory quality shows a negative effect on tax revenues. Meanwhile, agricultural variables do not show a significant effect on tax revenues. The recommendation from this study is that governments in N-11 countries focus on compiling good regulations in other sectors, such as agriculture because it is proven to increase tax revenues. In addition, the government also needs to encourage foreign investment in N-11 countries because based on the test results it will increase tax revenues.